1991
DOI: 10.3171/jns.1991.74.1.0064
|View full text |Cite
|
Sign up to set email alerts
|

Shunt surgery for hydrocephalus in tuberculous meningitis: a long-term follow-up study

Abstract: Hydrocephalus is a common complication of tuberculous meningitis. Case studies of 114 patients with tuberculous meningitis and hydrocephalus, who underwent shunt surgery between July, 1975, and June, 1986, were reviewed to evaluate the long-term outcome and to outline a management protocol for these patients based on the results. Seven factors were studied in each case: 1) age at admission; 2) grade on admission (I to IV, classified by the authors; Grade I being the best and Grade IV being the worst); 3) durat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
89
2
3

Year Published

1998
1998
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(99 citation statements)
references
References 14 publications
5
89
2
3
Order By: Relevance
“…7 Palur et al reported that 26 of 114 (22.8%) patients had to undergo one or more shunt revisions, one patient requiring more than three revisions. 8 Sil and Chatterjee reported a shunt infection rate of 15.6% and revision rate of 43.8% in their series of 37 children who underwent shunt surgery for TBM with hydrocephalus. Multiple revisions were done in 18.7% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…7 Palur et al reported that 26 of 114 (22.8%) patients had to undergo one or more shunt revisions, one patient requiring more than three revisions. 8 Sil and Chatterjee reported a shunt infection rate of 15.6% and revision rate of 43.8% in their series of 37 children who underwent shunt surgery for TBM with hydrocephalus. Multiple revisions were done in 18.7% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…The role of VPS and the timing of its use in children are controversial. Several groups have advocated performing VPS early in the clinical course of hydrocephalus, especially in mild-to moderate-grade cases (grade I/II/III according to the neurosurgical grading system described by Palur et al) (147) and performing a trial of external drainage in extremely poorgrade cases (grade IV cases) (95, 126, 147), whereas others endorse VPS only for those with noncommunicating hydrocephalus or those failing antibiotic therapy with communicating hydrocephalus (109,183). When the role of VPS has been examined for TBM-associated hydrocephalus, success rates ranged between 40 to 50%, and VPS has a complication rate of around 30% (1,109).…”
Section: Surgical Therapymentioning
confidence: 99%
“…The basal exudates of chronic meningitis are usually most severe at the circle of Willis, which might explain why cerebral infarctions are frequently located in this area [40,41].…”
Section: Discussionmentioning
confidence: 99%